Awareness perceptions among managements, teachers and school staffs related to safety, health and environment aspects in special education primary schools / Maziah Borhanuddin - Maziah , Borhanuddin (2018)
Safety in school is the most important key issue around the world that has been discussed without ending. Recent studies show that there is lack of awareness about safety in this public service, especially for students and teachers. The purpose of this study is to evaluate awareness among management, teachers and school staff on safety, health and environmental practices; to identify the high-risk accident area in school and to recognize the main factors that contribute to accidents at school. This study use questionnaire, onsite observations and informal interview as instruments for collecting data and information. The data collected has been analyzed using Microsoft Excel to evaluate awareness safety practices of respondent. Respondent for this study consist of 88 persons from school staff including management, teachers, and staffs. This study are limited to five (5) school special education primary school in Selangor, Wilayah Persekutuan Kuala Lumpur and Wilayah Persekutuan Putrajaya. The results show that school staff had middle stages of awareness of safety, health, and environment due to low knowledge about safety practices among them. The study also found the high-risk accident occurs are at toilet and stairs area. Meanwhile, from the respondent feedback, it is agreed that the main factor that contribute accident according to safety physical environment at school; safety during teaching lesson; and safety during outdoor activities is different by school according to type disability of the student, school condition and environment of the surrounding of school. At the end of this study, some recommendation has been suggested in this study i.e. require safety course attendance in key performance indicator (KPI) to all staff to enhance awareness safety practices to all school staffs.